CONFUCIAN CENTER DI KALIMANTAN BARAT - Changniaga, Sac Sanayan; Pebriano, Valentinus; Irwin, Irwin (JMARS: Jurnal Mosaik Arsitektur, 2026)
The Confucian Center is a place to support various religious and cultural activities for adherents of the Confucian religion. This facility serves as a platform for the practice and dissemination of Confucian teachings, which are rooted in the philosophy and teachings of Confucius. The center's functions include religious rituals, education, social activities, and recreation. The Confucian Center includes various facilities such as the Litang (living hall) as a place of worship, a learning area for education, a foundation office for administration, and a park for recreation. The design process for this center begins with data collection, analysis, and building design. The design approach used at the Confucian Center in West Kalimantan is Chinese architecture with feng shui principles. Feng shui concepts will be applied to the Litang and its surrounding areas. This Chinese architectural approach is based on building designs that reflect the values, traditions, and cultural identity of Chinese Indonesians, while also maintaining a balance between natural elements and the surrounding environment. An example of this approach is the courtyard within the center, which serves as the main access to the interior. The design results demonstrate that this center can facilitate Confucian followers in carrying out their activities. This center is expected to accommodate Confucian followers in West Kalimantan in their activities.